2017
DOI: 10.1215/00127094-0000003x
|View full text |Cite
|
Sign up to set email alerts
|

Open Gromov–Witten invariants, mirror maps, and Seidel representations for toric manifolds

Abstract: Let X be a compact toric Kähler manifold with −K X nef. Let L ⊂ X be a regular fiber of the moment map of the Hamiltonian torus action on X. Fukaya-Oh-Ohta-Ono [12] defined open Gromov-Witten (GW) invariants of X as virtual counts of holomorphic discs with Lagrangian boundary condition L. We prove a formula which equates such open GW invariants with closed GW invariants of certain X-bundles over P 1 used to construct the Seidel representations [31,29] for X. We apply this formula and degeneration techniques t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 24 publications
6
48
0
Order By: Relevance
“…While some general foundational work has been done [65,73], at this point most of the results in the theory rely on additional structure. In [21,22] Lagrangian Floer theory is employed to study the case when the boundary condition is a fiber of the moment map. In the toric context, a mathematical approach [13,33,54,68] to construct operatively a virtual counting theory of open maps is via the use of localization [3,4,8,41,59], quantum knot invariants [47,62], and ordinary Gromov-Witten and DonaldsonThomas theory via "gluing along the boundary" [2,60,63].…”
Section: 2mentioning
confidence: 99%
“…While some general foundational work has been done [65,73], at this point most of the results in the theory rely on additional structure. In [21,22] Lagrangian Floer theory is employed to study the case when the boundary condition is a fiber of the moment map. In the toric context, a mathematical approach [13,33,54,68] to construct operatively a virtual counting theory of open maps is via the use of localization [3,4,8,41,59], quantum knot invariants [47,62], and ordinary Gromov-Witten and DonaldsonThomas theory via "gluing along the boundary" [2,60,63].…”
Section: 2mentioning
confidence: 99%
“…Enumerative meaning of the mirror map 4 was obtained in the compact semi-Fano toric case and toric Calabi-Yau case [CLT13,CLLT11,CLLT12,CCLT]. It was shown that the mirror map equals to the so-called SYZ map, which arises from SYZ construction and is written in terms of disc invariants.…”
Section: Algorithm To Count Polygonsmentioning
confidence: 99%
“…In more explicit terms, coefficients of W LF are virtual counts of Maslov index 2 stable disks, or more precisely, genus 0 open Gromov-Witten invariants, and W LF is a perturbation of the Hori-Vafa potential W of the form W LF = W + correction terms because coefficients of W only encode counts of embedded disks (which is why W LF = W only when X is toric Fano). In general it is very hard to compute W LF , but explicit formulas are known in a few low-dimensional examples [2,22,6] and when X is semi-Fano [7,8,28].…”
Section: Introductionmentioning
confidence: 99%